Laparoscopic Cholecystectomy for Large/Giant Gallstones: Case Report and Brief Review of Literature - Shrestha, Anup; Bhattarai, Shachee; Shrestha, Shreya; Chand, Manoj; Bhattarai, Abhishek (Nepal Mediciti Medical Journal, 2021)
Gallstones disease are the most common biliary pathology. Its prevalence in Nepal is found to be 4.87%. Giant/large gallstones have a higher risk of complications and presents technical difficulties during laparoscopic cholecystectomy. Open cholecystectomy is preferred in most of the cases with giant gallstones. With the availability of experience laparoscopic surgeon and modern laparoscopic equipment, laparoscopic cholecystectomy is also feasible in large/giant gallstones. We report 2 cases, one large gallstone in 51 years old female and one giant gallstone in 39 years old female each of which were successfully managed laparoscopically with uneventful post-operative period.